2021
DOI: 10.1038/s41598-021-90265-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 diagnosis by routine blood tests using machine learning

Abstract: Physicians taking care of patients with COVID-19 have described different changes in routine blood parameters. However, these changes hinder them from performing COVID-19 diagnoses. We constructed a machine learning model for COVID-19 diagnosis that was based and cross-validated on the routine blood tests of 5333 patients with various bacterial and viral infections, and 160 COVID-19-positive patients. We selected the operational ROC point at a sensitivity of 81.9% and a specificity of 97.9%. The cross-validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
132
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 40 publications
0
132
0
Order By: Relevance
“…Following the December of 2019, the SARS-CoV-2 first reported in Wuhan, China [1] , [4] , [5] , [6] , [7] , [9] , [10] caused a pandemic (declared by World Health Organization (WHO) on March 11th, 2020) [1] , [5] , [9] by inducing respiratory infection (called COVID-19) with symptoms typical of fever, tiredness, and coughs [5] , [7] , [9] . While being highly contagious [1] , in some cases, COVID-19 infection could be asymptomatic making it capable of spreading at an increasing pace [2] , [6] , [7] . This poses a challenge to most of the countries worldwide with a much more burden on developing and less-developed countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the December of 2019, the SARS-CoV-2 first reported in Wuhan, China [1] , [4] , [5] , [6] , [7] , [9] , [10] caused a pandemic (declared by World Health Organization (WHO) on March 11th, 2020) [1] , [5] , [9] by inducing respiratory infection (called COVID-19) with symptoms typical of fever, tiredness, and coughs [5] , [7] , [9] . While being highly contagious [1] , in some cases, COVID-19 infection could be asymptomatic making it capable of spreading at an increasing pace [2] , [6] , [7] . This poses a challenge to most of the countries worldwide with a much more burden on developing and less-developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, developed countries have faster and more comprehensive access to vaccines, while other countries are facing multiple hindrances progressing in vaccination course of action like shortage of sufficient vaccine doses for the vaccination of vulnerable groups. Moreover, there are still no confirmed medications to cure patients infected with COVID-19 [1] . Thus, the importance of screening patients suspected to be infected with the SARS-CoV-2 has not declined [1] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the number of cases increases and more data becomes available, various researches [1] , [2] , [3] , [4] , [5] , [6] , [7] develop a range of mathematical models or employ machine learning algorithms to forecast the transmission of SARS-CoV-2. Previous studies have also employed LSTM [8] , [9] , [10] , [11] , [12] or XGBoost [13] , [14] , [15] , [16] , [17] , [18] , [19] models to forecast the spread of COVID-19 and identify the most influential COVID-19 indicators. Chimmua et al [8] adopted LSTM algorithm to forecast confirmed cases in Canada within next two weeks and emphasized the significant role of social distance regular.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the impact of the COVID-19 pandemic on driving behavior, the authors [18] utilized explanatory XGBoost feature importance to evaluate the influence of COVID-19 and used seasonal ARIMA models to model. Kukar et al [19] used random forest, deep neural networks, and XGBoost algorithms to build models that predicted COVID-19 diagnosis based on regular blood test results, age, and gender. To the best of our knowledge, few studies have used the combined LSTM networks and XGBoost models to predict infectious diseases in time series analysis.…”
Section: Introductionmentioning
confidence: 99%